1973
DOI: 10.1136/jcp.26.6.396
|View full text |Cite
|
Sign up to set email alerts
|

Septicaemia due toPasteurella pneumotropica

Abstract: The literature concerningPasteurella pneumotropicainfection in animals and man is briefly reviewed and a case presented in which the organism was the cause of septicaemia in a patient receiving chemotherapy for myeloid leukaemia. Bacteriological findings are recorded and compared with those of other authors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

1979
1979
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…It has also been isolated from humans having infections associated with animal contact, usually traumatic exposure in the form of bites. Although rare, reported human infections include meningitis [9], bone and joint infections [10], wound infections and cellulitis [11], septicemia [12], and pneumonia [13]. We found no reports of peritonitis due to P. pneumotropica.…”
Section: Case Reportmentioning
confidence: 79%
“…It has also been isolated from humans having infections associated with animal contact, usually traumatic exposure in the form of bites. Although rare, reported human infections include meningitis [9], bone and joint infections [10], wound infections and cellulitis [11], septicemia [12], and pneumonia [13]. We found no reports of peritonitis due to P. pneumotropica.…”
Section: Case Reportmentioning
confidence: 79%
“…Similarly, P. multocida was isolated from a wound after a bite from a laboratory rat, although the organism was not found in subsequent cultures from the rat (Bergogne- 1972). Septicemia and meningitis due to pas teurella have also been reported (Cooper et aL, 1973;Rogers et aL, 1973). Hubbert and Rosen (1970) listed 316 cases of P. multocida in man, usually associated with animal exposure.…”
Section: Clinical Signs Susceptibility and Resistance In Manmentioning
confidence: 99%
“…In a review of the English-language literature, we found sporadic case reports of human infections with P. pneumotropica, such as endocarditis (3), cellulitis (1), bone and joint infections (8,20), meningitis (16), skin infections (15), peritonitis in a dialysis patient (4), and pneumonia in a patient with AIDS (5). One case of septicemia in a patient receiving chemotherapy for myeloid leukemia was reported in 1973 (19). Another case, involving a patient who contracted meningitis following a dog bite, suggested the occurrence of bacteremia in the pathogenesis of the infection (16).…”
mentioning
confidence: 99%
“…The presence of P. pneumotropica is sometimes reported in the respiratory floras of persons who have pets, especially if these individuals have some underlying disease, such as cirrhosis, or a neoplasm (5,19). In a review of the English-language literature, we found sporadic case reports of human infections with P. pneumotropica, such as endocarditis (3), cellulitis (1), bone and joint infections (8,20), meningitis (16), skin infections (15), peritonitis in a dialysis patient (4), and pneumonia in a patient with AIDS (5).…”
mentioning
confidence: 99%